2019
DOI: 10.1016/j.cjtee.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of forearm diaphyseal defect by distraction compression bone transport and continued distraction for radial head reduction: A case study

Abstract: Treatment of infected forearm nonunion and defects represents a difficult task for the operating surgeons. Conventional methods like composite and vascularized fibular grafts and the induced membranes filled with cancellous autografts or the Masquelet technique have been reported to be useful and successful, but sometimes it is difficult to predict the outcome and cannot address simultaneous deformities or the need to apply gradual distraction for reduction of a chronically dislocated radial head. Ilizarov tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The forearm is a complex joint mechanism and not just two separate bones. The integrity of the anatomical structures is vital for a comprehensive function and synergistic effect, especially for the pronation and supination [ 28 ]. There is no doubt that the management of a segmental diaphyseal defect in the forearm is a difficult task for surgeons, especially combined with deep infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The forearm is a complex joint mechanism and not just two separate bones. The integrity of the anatomical structures is vital for a comprehensive function and synergistic effect, especially for the pronation and supination [ 28 ]. There is no doubt that the management of a segmental diaphyseal defect in the forearm is a difficult task for surgeons, especially combined with deep infection.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfactory outcomes the two studies above gained, while failed to provide more detailed functional scores at the last clinical visit. Recently, Kliushin et al [ 28 ] also reported a 43 years old man with an infected ulnar defect and dislocated radial head due to infected Monteggia fracture, and the patient was successfully treated by Ilizarov bone transport after failed attempts by a bone spacer and fibular graft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The forearm is a complex joint mechanism and not just two separate bones. The integrity of the anatomical structures is vital for a comprehensive function and synergistic effect, especially for the pronation and supination 22 . There is no doubt that the management of a segmental diaphyseal defect in the forearm is a di cult task for surgeons, especially combined with deep infection.…”
Section: Discussionmentioning
confidence: 99%
“…The Ilizarov segmental bone transport technique can be applied in the reconstruction of the bone defects of any length theoretically with less invasive fashion and more versatility compared to other methods, especially for massive bone defects > 6 cm. Most studies about applying the Ilizarov technique in the treatment of bone defects were focused on the lower extremity [12][13][14][15][16][17][18][19] , and there are few published data reported in upper extremity 1,3,[20][21][22][23] . Compared with the lower limbs, the upper limbs require more function than weight-bearing.…”
Section: Introductionmentioning
confidence: 99%